Defining Special Care - Gifford, Ben (2020)
For the better part of the last century, the Supreme Court has held that courts must evaluate the voluntariness of juvenile confessions with “special care.” This special care requirement cautions courts against judging juveniles “by the more exacting standards of maturity” or comparing a juvenile suspect “with an adult in full possession of his senses and knowledgeable of the consequences of his admissions.” It also instructs courts to ensure that a juvenile’s “admission was voluntary, in the sense not only that it was not coerced or suggested, but also that it was not the product of ignorance of rights or of adolescent fantasy, fright or despair.” Despite the force with which the Supreme Court has spoken on the issue, lower courts regularly fail to follow the special care mandate. Some overlook the standard altogether, while others only pay lip service to it, and still others misconstrue it and disregard it on mistaken grounds. The result in any of these cases is that lower courts assess the voluntariness of juvenile confessions in the same way they would evaluate confessions obtained from adults, not with the heightened degree of scrutiny that Supreme Court precedent requires. In order to tether courts more firmly to the mast of special care, this Article highlights specific factors that courts should consider when evaluating the voluntariness of juvenile confessions. By framing their analyses in terms of these factors, courts can hopefully begin to evaluate juvenile confessions with the requisite level of care